SVC Is a Marker of Respiratory Decline Function, Similar to FVC, in Patients With ALS - Pinto, Susana; de Carvalho, Mamede (Frontiers in Neurology, 2019)
Introduction Respiratory function is a critical predictor of survival in amyotrophic lateral sclerosis (ALS). The role of respiratory function as predictor of functional decay in ALS is not fully established. We aimed to determine if slow vital capacity (SVC) is a predictor of functional loss in ALS. Methods Consecutive ALS patients in whom respiratory tests were performed at baseline and 6 months later were included. All patients were evaluated with revised ALS functional rating scale (ALSFRS-R) and with the respiratory tests, SVC and forced vital capacity (FVC). Significant independent variables of functional decay as determined by an ALSFRS value lower than 0.92/month were assessed by univariate Kaplan-Meier log-rank test and multivariate Cox proportional hazards model. Results We included 232 patients (134 men; mean onset-age 59.1±11.23 years; mean disease duration from first symptoms to first visit: 14.5±12.9months; 166 spinal and 66 bulbar onset). All variables studied declined significantly between the two evaluations (p<0.001). FVC and SVC were strongly correlated at study entry (r2=0.98, p<0.001) and FVC and SVC decays between first evaluation and six months after were the only significant prognostic variables of functional decay (p<0.001). Conclusion FVC and SVC decay are inter-changeable in predicting functional decay in ALS. Any pharmacological intervention reducing the rate of FVC and SCV decline should have a positive impact on the global functional impairment, which has relevant implications for clinical trials design and interpretation.